СОВРЕМЕННЫЕ ВЗГЛЯДЫ НА КОНВЕРСИЮ ПРИ ЛАПАРОСКОПИЧЕСКОЙ ХОЛЕЦИСТЭКТОМИИ - V. V. Kryzhevskii; Yu. V. Pavlovich; N. A. Mendel (Клінічна хірургія, 2017)
СОВРЕМЕННЫЕ ВЗГЛЯДЫ НА КОНВЕРСИЮ ПРИ ЛАПАРОСКОПИЧЕСКОЙ ХОЛЕЦИСТЭКТОМИИ